Harnessing theta waves: tACS as a breakthrough in alleviating post-stroke chronic pain - Song, Ningjing; Long, Ling; Liu, Nianquan; Luo, Yujun; Wei, Meng; Huang, Hai; Liu, Wan (Frontiers in Neuroscience, 2025)
Neural oscillations play a critical role in the regulation of brain functions, with theta waves (4–8 Hz) in the sensorimotor cortex significantly influencing pain perception and modulation. These oscillations can modulate pain signal transmission, emotional cognition, and neuroplasticity. Post-stroke chronic pain is a common and complex symptom that imposes significant physiological and psychological burdens on patients. Transcranial alternating current stimulation (tACS), a non-invasive brain stimulation technique, can synchronize specific frequency neural activities, reorganize brain networks, and modulate neuroplasticity by adjusting specific frequency neural oscillations. In recent years, tACS has been widely applied in the research and treatment of various neurological and psychiatric disorders. This study aims to systematically summarize the current research progress on the regulation of θ oscillations in sensorimotor cortex by tACS. By reviewing relevant experimental and clinical studies, we explore the specific mechanisms of θ oscillations in pain perception and modulation and analyze the mechanisms and effects of tACS modulation of θ oscillations. Additionally, we examine the central and peripheral neural mechanisms of post-stroke chronic pain, emphasizing the critical role of the sensorimotor cortex in pain processing. In conclusion, tACS shows potential for modulating sensorimotor cortex θ oscillations and alleviating post-stroke chronic pain. This research provides new insights into the neural modulation mechanisms related to pain and offers potential new directions for developing novel therapies. Future clinical studies and technological optimizations are necessary to ensure the effectiveness and feasibility of tACS in clinical practice.